Organometallic C C Coupling Reactions for Porphyrins - SENGE, MATHIAS (World Scientific/Imperial College Press, 2010)
Organometallic reactions play an important role in modern synthetic chemistry. The ability to form a C?C bond in just one step makes this synthetic approach one of the most attractive tools to create or to modify organic molecules.1,2 Despite many methods available there is still a high demand for new and more effective synthetic strategies. The emerging new transition metal catalysts with widespread activities expand the variety of functionalities to be introduced into the substrates and allow the preparation of more elaborate and multifunctional synthons.3-5 Thus, applications of metal-catalyzed coupling reactions continue to grow rapidly providing an easy access to novel heteroatomic building blocks.6,7
Handbook of Porphyrin Science, Vol. III
PUBLISHED
Keywords: porphyrins